A first comprehensive look at the order-disorder nature of RTK KIT native and carcinogenic targets - Luba Tchertanov; Julie Ledoux (Global Journal of Cancer Therapy - Peertechz Publications, 2022)
Receptors Tyrosine Kinases (RTKs) act as sensors for extracellular ligands, the binding of which triggers dimerization, activation, and autophosphorylation of specific tyrosine (Y) residues in the Cytoplasmic Domain (CD). This leads to the recruitment and activation of multiple downstream signaling proteins, which regulate various aspects of cellular physiology.